Implementation of The Problem based Learning (PBL) Model on Students' Mathematical Connection Abilities - Ridwan, Muhamad Asep; Kusnandi, K (Proceedings International Conference on Education Innovation and Social Science, 2025)
This research was conducted with the aim of identifying, describing, and analyzing findings from various studies discussing the implementation of the Problem-Based Learning (PBL) model in impoving students mathematical connection skills. The method used was a systematic Literatur Review (SLR), which allowed researchers to comprehensively examine various relevant primary literatur. The data collection Process was carried out through the stages of selecting scientific articles based on predetermined inclusion criteria, and a total of 18 articles were declared eligible for further analysis. The selected articles were classified based on educational level, methodological approach, and the impact of PBL implementation on students' mathematical connection skills. The research findings showed that the implementation of the PBL model consistently had a positive influence on improving mathematical connection skills, especially in junior high school students. In addition, a quantitative approach with experimental and quasi-experimental designs was the most widely used method in measuring the effectiveness of the PBL model. These results indicate that PBL is a potential pedagogical approach in supporting the development of students' mathematical connection skills at various educational level.